Age and gender differences in health risk perception - Kim, YoungHo; Park, InKyoung; Kang, SooJin (Central European journal of public health, 2018)
OBJECTIVE: The current study investigated how adolescents perceive their own health risks and compare their own likelihood of health risks with that of others of the same age. Moreover, the study identified the differences in health risk perceptions between males and females. METHODS: A total of 625 adolescents (314 males and 311 females) from the Nowon district, geographically located in northern Seoul, voluntarily participated. In order to measure health risk perceptions a Korean version of self-other risk judgments profile was used. RESULTS: The findings indicated that study participants, regardless of gender and age, tend to underestimate their vulnerability to majority of health risk events. Furthermore, there were significant gender and age differences in health risk perception and perception bias in all health risk domains. CONCLUSION: The present study suggests that further research is needed to identify realistic and unrealistic perception mechanism for a large number of people from different demographic and socioeconomic backgrounds.
Keywords: Risk-Taking; adolescents; Republic of Korea; mladiství; sexuální faktory; Risk Assessment; průzkumy a dotazníky; mužské pohlaví; risk perception; age; Health Knowledge, Attitudes, Practice; věkové faktory; Asian People; gender; ženské pohlaví; hodnocení rizik; Humans; Sex Factors; perception bias; Surveys and Questionnaires; Age Factors; zdraví - znalosti, postoje, praxe; riskování; Korejská republika; Female; health risks; Adolescent; Asijci; lidé; Male